AN ANALYSIS OF TECHNICAL TOOLS IN TRANSLATION PROCEDURES USED IN HARRY POTTER FIRST NOVEL - Marisa Fran Lina (Universitas Sebelas Maret, 2019)
Translating a novel becomes popular nowadays. Meanwhile, there are four technical tools in the translation procedures which are ordinaryly used by the translator; addition, subtraction, elimination and adaptation. Thus, the purpose of this research is to find the four technical tools in Listiana Srisanti’s translation result appeared in the first novel of Harry Potter. Library research is considered as the method of collecting data. The data in the novel that have been collected are analyzed by using the four technical tools. Based on the classification, it is discovered that there are ten data of addition, thirteen data of subtraction, twelve data of adaptation and nine data of elimination. Those data found are representative enough from the whole data in the novel, because the author takes the data by its part from the translated sentences contained the technical tools. In conclusion, the result indicates that the technical tool of subtraction is the most considerable data (13) applied in the novel.